From dugouts to double outriggers; Lexical insights into the development of Swahili nautical technology - Walsh, Martin (UI Scholars Hub, 2021)
The early history of nautical technology in the western Indian Ocean and adjoining parts of the eastern Africa coast is poorly understood. In the absence of evidence from shipwrecks, it has hitherto been based largely on the uncertain interpretation of a few documentary references and speculation surrounding technological parallels and assumed lexical resemblances. This paper examines some of the linguistic evidence in a more rigorous way, by undertaking a cross-dialectal comparison of names for watercraft and terms for outriggers in Swahili (Kiswahili), a Bantu language spoken on the islands and in scattered communities along the western seaboard of the Indian Ocean. The resulting analysis provides a new outline of the development of Swahili nautical technology and maritime culture, highlighting the key role played by particular boat forms, and the relative importance of indigenous innovation and different external influences, including the elusive impacts of Austronesian seafaring.